المدخل الاتصالي في تعليم اللغة العربية - Asy’ari, Hasyim (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2018)
Humans need language in order to interact with society. They express their thoughts and intentions with language. Language is a communication tool in society.  And learning a foreign language not only learns grammar, but the ability to communicate with other communities. The approach that fits this purpose is the communicative approach. Communicative is the process of conveying thoughts and perceived by speech methods that include meaningful writing and a clear subject of thought. This approach aims to develop language competence in general by directing learners to language functions. Communicative ability is one's ability to grammatical adjustment and its use for certain communicative functions with cra corresponding to a particular place.